Identification of out-of-plane material characteristics through sheet-metal blanking - Bolka, Špela (Strojniški vestnik, 2015)
The mechanical characteristics of sheet metals are typically identified in the in-plane direction, although the sheet-metal forming processes (e.g., blanking, deep-drawing) are normally applied in the out-of-plane direction. As the mechanical characteristics are not necessarily constant, their direct experimental evaluation through the forming process would enable material monitoring and process optimization, and, additionally, material characterization in the out-of-plane direction. Full, partial (to a certain depth) and sequential (consecutive partial steps to full penetration) blanking experiments are performed on a laboratory blanking apparatus to correlate the out-of-plane material characteristics with the in-plane ones. The well-established in-plane approach to damage is introduced for the out-of-plane direction to determine the isotropic Lemaitre damage variable. Furthermore, yield and ultimate shear stresses are determined and correlated to their respective in-plane counterparts, offering a new insight in the sheet-metal blanking process.
Keywords: eksperimenti; elasto-plastični materiali; konstitutivne relacije; mehanski testi; preoblikovanje; rezanje; žilavi lom